JOB ANALYSIS, WORKLOAD ANALYSIS, AND EMPLOYEE’S NEEDS PLANNING DETERMINANT OF EMPLOYEE PERFORMANCE OF CIVIL SERVANT - Faizal, Riza (JURNAL PUNDI, 2019)
The puprpose of this study was to determine to analyze : (1) job analysis, workload analysis, employee’s needs planning and employee performance civil servant in Tasikmalaya Regency. (2) Effect of partially or simultaneously work analysis, workload analysis, employee’s needs planning employee’s needs planning for employee performance in Tasikmalaya Regency.            The method used was descriptive method. The data collection techniques used were questionnaires, depth interviews, and documentation. The sampling tecnique used is a census with a sample size that was 100 (one hundred) respondents. The analytical tool used was path analysis.            Based on the result in disccusion in mind that job anlysis, workload analysis, employee’s needs planning and performance of employees in Tasikmalaya Regency included in good classification. There is positive effect of job analysis, workload analysis, employee’s needs planning partially or simultaneously on the performance of employees in the Tasikmalaya Regency. So, Hypothesis were veryfied.